Transformasi Pendidikan Islam Di India Dari Kejayaan Hingga Kemunduran Dinasti Mughal - Dwi Utami, Prabawati (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2025)
The Mughal dynasty in India, founded by Babur and reaching its peak under the leadership of Sultan Akbar the Great, was known for its tolerant policies that had a significant impact on Indian history. It ranged from glory under Akbar, Jahangir and Shah Jahan, to decline triggered by weak governance and Aurangzeb's controversial policies towards non-Muslims. They made major contributions in areas such as economics, art, architecture, science and the judicial system. The focus of this research is to understand both the glory and decline of the Mughal Dynasty and the historical legacy they left behind. This research method is conducted through literature review with the aim of analyzing the contribution of the Mughal dynasty in various aspects of life in Indian society as well as the transformation of Islamic education that occurred during its heyday. Despite suffering setbacks due to weak governance and resistance to British invaders, their historical and civilizational legacy remains influential in India to this day, with the Taj Mahal as one of their famous relics. Thus this study not only highlights the History of the Mughal Dynasty, but highlights the relevance of Islamic Education in India during the Mughal Dynasty which reflects an attempt to harmonize Islamic values according to the demands of the times.